EDUKASI JAJANAN SEHAT DAN CARA MENCUCI TANGAN UNTUK MENCEGAH DIARE PADA SISWA SEKOLAH DASAR - Padmiswari Anak Agung (ASMAT: Jurnal Pengabmas, 2023)
Snacks play an important role in providing energy and other nutrients to school-age children. Due to the high activity level of children, the consumption of snacks in school-age children must be considered. Part of children's hygiene is having good and proper hand washing habits to avoid any form of infection. Washing hands with soap can reduce the risk of infection by almost 50%. However, many people do not understand the importance of washing their hands. Education activities for healthy snacks and hand washing to prevent diarrhea are very important in SD Negeri 21 Dauh Puri. Forty-six sixth graders participated in the activities and received counseling. To measure the success of the activity, students were asked to complete a pre and posttest consisting of 10 questions about healthy snacks and hand washing to prevent diarrhea. This activity was successful because students' knowledge of healthy snacks and hand washing to prevent diarrhea was greatly increased. Assistance of teachers and parents with these activities must continue to improve the knowledge of elementary school children. Keywords: healthy snacks, washing hands, diarrhea, elementary school students